2006
DOI: 10.1242/dev.02463
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Arabidopsis tapetum development and function by DYSFUNCTIONAL TAPETUM1 (DYT1) encoding a putative bHLH transcription factor

Abstract: In flowering plants, male fertility depends on proper cell differentiation in the anther. However, relatively little is known about the genes that regulate anther cell differentiation and function. Here, we report the analysis of a new Arabidopsis male sterile mutant, dysfunctional tapetum1 (dyt1). The dyt1 mutant exhibits abnormal anther morphology beginning at anther stage 4, with tapetal cells that have excess and/or enlarged vacuoles and lack the densely stained cytoplasm typical of normal tapetal cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
407
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 405 publications
(423 citation statements)
references
References 45 publications
13
407
1
2
Order By: Relevance
“…S2) showed that the cdm1 tapetum morphology appeared normal and different from known mutants (e.g. dyt1 and ams) with defective tapetum (Sorensen et al, 2003;Zhang et al, 2006). In addition, our microarray analysis did not detect dramatic expression changes for genes known to be important for tapetum development, such as AMS and MS188.…”
Section: Pollen Wall Formation Was Defective In Cdm1mentioning
confidence: 57%
“…S2) showed that the cdm1 tapetum morphology appeared normal and different from known mutants (e.g. dyt1 and ams) with defective tapetum (Sorensen et al, 2003;Zhang et al, 2006). In addition, our microarray analysis did not detect dramatic expression changes for genes known to be important for tapetum development, such as AMS and MS188.…”
Section: Pollen Wall Formation Was Defective In Cdm1mentioning
confidence: 57%
“…An Arabidopsis basic helix-loop-helix (bHLH) transcription factor DYSFUNCTIONAL TAPETUM1 (DYT1) and its rice ortholog UNDEVELOPED TAPETUM1 (UDT1) are required for the differentiation of tapetum. In dyt1 and udt1 mutants, tapetal cells become abnormally vacuolated and hypertrophic later (Jung et al, 2005;Zhang et al, 2006;Feng et al, 2012). How DYT1 and UDT1 regulate tapetum differentiation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Tapetal cell development and differentiation are critical for the early events in male reproduction, including meiosis; however, during late pollen development, tapetal degeneration, triggered by an apoptosis-like process, is also vital for viable pollen formation (Papini et al, 1999;Varnier et al, 2005;Li et al, 2006;Aya et al, 2009). Currently, although several genes encoding putative transcription factors have been reported to be associated with tapetal function and degeneration, such as Arabidopsis (Arabidopsis thaliana) MYB33/MYB65 (Millar and Gubler, 2005), DYSFUNCTIONAL TAPETUM1 (DYT1; Zhang et al, 2006), ABORTED MICROSPORE (AMS; Sorensen et al, 2003;Xu et al, 2010), and MALE STERILITY1 (MS1; Wilson et al, 2001;Ito and Shinozaki, 2002) and rice (Oryza sativa) GAMYB (Kaneko et al, 2004;Aya et al, 2009;Liu et al, 2010), UNDEVELOPED TAPETUM1 (UDT1; Jung et al, 2005), TAPETUM DE-GENERATION RETARDATION (TDR; Li et al, 2006), and MADS3 (Hu et al, 2011), their detailed functional roles in regulating tapetal PCD during anther development are unclear. We have shown that the Arabidopsis ms1 mutant displays altered tapetal development, with a lack of normal PCD and abnormal tapetal degeneration associated with large autophagic vacuoles and mitochondrial swelling (Vizcay-Barrena and Wilson, 2006).…”
mentioning
confidence: 99%